The Portrait of English Teaching Grounded in Interculturality - Ramsa Aryadi; Jumatul Hidayah; Sarwo Edy (Universitas Bengkulu, 2020)
This study aimed to analyze English teaching based on the perspective of intercultural language teaching (ILT). The ILT perspective was referred to Liddicoat and Scarino's (2013) model. Three English teachers from one of the schools in Kepahiang District were engaged as the participants of this study. This study applied a qualitative method. The data were collected using observation. The findings of this study revealed that the teachers had applied three principles of ILT, namely active construction, making connections, and interaction. Active construction was represented by some activities such as word quiz, the use of cultures-embedded materials, group work, pair-work communication, and check and recheck with partners. Making connection principle was portrayed from some activities such as directing questions and cultural comparison. Interaction principle was depicted from some activities such as the use of cultures-embedded texts, group-interaction, pair-wok communication, and check and recheck with partners. It is recommended that further studies be conducted by involving more participants so that richer data with their varieties can be portrayed.